Circular lining behaviour due to earthquake load in MRT Jakarta underground tunnel area CP-106. Issue 1 (September 2020) - Muhammad, F; Prakoso, W A
Abstract: One solution to traffic congestion in Jakarta is to build a mass transportation system in the form of Mass Rapid Transit (MRT), especially the application of underground tunnel structures. This study examines the modeling of tunnel behavior on the effect of earthquake loads. This study calculates circular tunnel behavior in static and dynamic conditions due to earthquake effects. Static condition analysis using Muir Wood's theory and dynamic conditions using the theories of Wang (1993) and Panzien (2000) as well as supported by empiric and numeric calculations. The depth of the MRT tunnel in the CP-106 area is at a depth of 11 meters by diverting by clay with NSPT 3-20. The results show that in static condition has tunnel deformation that works at 8.06 mm in empiric and 15.12 mm in numeric. In the dynamic analysis with earthquake acceleration in 300 cm/s 2 produces oval deformation at 15.95 mm in empiric and 15.20 mm in numeric. The maximum deformation limit given is 20 mm with a maximum earthquake acceleration value of 400 cm/s 2 . In conclusion, MRT Jakarta area CP-106 in static condition has a lower deformation than dynamic conditions, but both conditions fulfill the deformation tunnel requirements.